Pengaruh Media Pembelajaran Audio Visual Terhadap Peningkatan Prestasi Peserta Didik Sekolah Minggu di Kabupaten Pesawaran Lampung - Dhamayanti, Novita; Dhamayanti, Wina (Jounal Nyanadassana, 2024)
This study aims to investigate the impact of audio-visual learning aids on enhancing the academic performance of students attending Girikirti Vihara Sunday School. Employing an experimental design with a quantitative approach, the study utilized a questionnaire administered to 12 students spanning from fourth grade elementary to third grade junior high school. Data collected through the questionnaires were analyzed using a Likert scale, while the effects of visual, audio, and audio-visual media on Buddhist religious values were assessed using the t-test. The findings reveal a significant positive correlation between the use of learning media (visual, audio, and audio-visual) and comprehension of Buddhist subjects, with achievement percentages of 85.41%, 81.25%, and 87.5%, respectively. Similarly, the impact on students' concentration during learning yielded percentages of 81.25%, 79.16%, and 83.33% for visual, audio, and audio-visual media, respectively. Moreover, the influence of these media on students' interest in Buddhist learning material was evident, with achievement percentages of 83.33%, 79.16%, and 85.41%. Regarding memory retention in Buddhist subjects, percentages of 77.08%, 81.25%, and 83.33% were achieved for visual, audio, and audio-visual media, respectively. Furthermore, the t-test analysis demonstrated a significant effect of learning media (visual, audio, and audio-visual) on the scores of Buddhist religious subjects at Girikirti Vihara Sunday School. These findings underscore the importance of utilizing effective learning media in the teaching process to enhance student achievement and comprehension.